2009
DOI: 10.1016/j.actamat.2009.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent transport in nanocomposite C:co films

Abstract: The magneto-transport properties of nanocomposite C:Co (15 and 40 at.% Co) thin films are investigated. The films were grown by ion beam co-sputtering on thermally oxidized silicon substrates in the temperature range from 200 to 500°C. Two major effects are reported: (i) a large anomalous Hall effect amounting to 2 lX cm, and (ii) a negative magnetoresistance. Both the field-dependent resistivity and Hall resistivity curves coincide with the rescaled magnetization curves, a finding that is consistent with spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The nc-Me/C films based on metals of this category are in general considered as good candidates for protective coating applications. 2,3,7-16 (ii) Metals with low affinity to carbon such as cobalt [22][23][24][25][26][27][28][29][30][31][32] and nickel. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Such ferromagnetic metals can form a soft and thermodynamically unstable metal carbide compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nc-Me/C films based on metals of this category are in general considered as good candidates for protective coating applications. 2,3,7-16 (ii) Metals with low affinity to carbon such as cobalt [22][23][24][25][26][27][28][29][30][31][32] and nickel. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Such ferromagnetic metals can form a soft and thermodynamically unstable metal carbide compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The nc-Me/C films based on such metals are in most of cases considered for studies due to the special magnetic properties of the ferromagnetic metals which make of this films suitable candidates for magnetic recording media applications. [22][23][24]29,33,36,44 In addition to their interesting magnetic behavior, several recent studies have demonstrated that this class of materials is quite interesting for the development of piezoresistive devices such as strain-gauge. 40,41 (iii) Metals non miscible with carbon such as platinum, 43,50 gold, 50 and copper.…”
Section: Introductionmentioning
confidence: 99%
“…Among nanocomposite films, carbon: transition metal (C:TM) nanocomposite films possess a combination of properties that make them promising candidates for sensors, 2,3 high-density magnetic recording media, 4-10 spintronic devices, 11,12 low-friction solid lubricants, hard wear-resistant coatings 10,[13][14][15][16][17][18][19] or as carbon-based plasma-facing materials for fusion reactors. 1 They are advanced functional materials whose mechanical, electrical, optical, and structural properties cannot be predicted from the properties of the individual components alone, but strongly depend on the composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…1 This is mainly associated with the high surface to volume ratio of the nanometer sized phase resulting in many interfaces between the constituent phases. Alternatively, the carbon matrix can be amorphous, 6,12,18,24 graphitelike with graphene layers curved into a cylindrical shape encapsulating elongated nanoparticles, [6][7][8][9][10][11][12][13]22,24 and fullerenelike with a spherical-like curvature encapsulating globular nanoparticles. 20 The structure of C:TM nanocomposite films consists of metal-rich nanoparticles embedded in a carbon matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposite films consisting of ferromagnetic nanoparticles embedded in a nonmagnetic matrix have been paid much attention due to its interesting properties originating from the finite-size and interface effects [1][2][3][4][5]. The giant magnetoresistance (GMR) has been observed in the heterogeneous magnetic nanostructures composed of magnetic and nonmagnetic metals, such as magnetic multilayers [6][7][8], spin valves [9] and nanocomposite films [10,11].…”
Section: Introductionmentioning
confidence: 99%